Wobec społecznego i kulturowego fenomenu "Chopinowskiego Igrzyska" - Bruliński, Michał (Res Facta Nova, 2020)
The article is a review of the book The Chopin Games on the history of the Fryderyk Chopin International Piano Competition 1927–2010. In the author’s opinion, the synthesis organizing selected cultural, social and anthropological aspects of the Chopin Competition was very useful, and it’s authors completed a large part of the tasks declared in the introduction to the work.